Implantable Tx–Rx wireless systems. An overview of their efficiency analysis through scattering matrix formalism - Koulouridis, Stavros (Comptes Rendus. Physique)
Looking at wireless implantable systems as a pair of or more Tx–Rx components, we discuss how their efficiency can be calculated in order to achieve an optimum result that can be evaluated over measurements and literature. To that end, scattering parameters’ notation is introduced instead of considerations of the gain, the propagation losses and the radiation patterns. Looking at the system as a black box, remarks on optimum link calculation in relation to frequency, antenna size, phantom use, matching circuit integration and efficiency intensifiers are being carried out. International standards for allowed power and safety levels are added to the discussion. Different scenarios including telemetry, wireless harvesting and sensor transmission information are included as examples.